Burkina Faso : Fourth and Fifth Reviews Under the Extended Credit Facility and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Burkina Faso. (IMF Staff Country Reports; Country Report ;, 2016)
This paper focuses on the economic developments, economic policies, and economic risks in Burkina Faso. Economic activity remained sluggish over the course of 2015 and in early 2016, amidst political uncertainty and weather shocks. The overall fiscal deficit increased by 0.3 percentage points of GDP compared with 2014, as the sharp decline in revenues was offset by expenditure compression. However, growth is projected to gradually recover in 2016, albeit at a slower rate than anticipated at the time of the 2nd/3rd Extended Credit Facility reviews. Fiscal policy in 2016 will remain prudent and anchored by the WAEMU convergence criterion. Moreover, the authorities are prioritizing measures to boost domestic revenue mobilization.